ANALISIS KESULITAN BELAJAR ILMU PENGETAHUAN SOSIAL PADA SISWA DI KELAS V SDN 27 KAMANG - Darsyifa Azahra; Nuraini Kumala Suri; Silvina Noviyanti (LPPM Universitas Muhammadiyah Muara Bungo, 2026)
This research aims to determine and describe the learning difficulties of class V students at SDN 27 Kamang. This research uses a descriptive qualitative approach. The theory used is the factors of learning difficulties. Data was obtained through interviews and documentation methods. The results of the research show that there are internal and external factors that cause Class V students at SDN 27 Kamang to experience difficulty learning social studies. Internal factors include students' difficulties in understanding the material or themes being taught, students' lack of interest in social studies lessons, lack of self-confidence to express opinions or ask questions, few students have good study habits. External factors are the lack of the role of a father or mother figure due to death, lack of parental attention and supervision in social studies subjects, a home atmosphere that is less supportive for learning, a lack of teacher ability to deliver material, and inadequate facilities and infrastructure. Efforts made to overcome the difficulties of class V students at SDN 27 Kamang are by reprimanding students who are not focused, providing ice breakers in the middle of the lesson, providing learning motivation, giving rewards to students who dare to try and giving sanctions to students who commit violations.